ISLAMIC CORPORATE GOVERNANCE DALAM LAPORAN TAHUNAN BANK SYARIAH DI INDONESIA - Nastiti, Ari Sita (Universitas Muhammadiyah Jember, 2018)
This study analyzed the level of Islamic Corporate Governance (ICG) disclosure in the annual report of Islamic banking in Indonesia. The level of ICG disclosure was measured using the Corporate Governance Disclosure Index (CGDI) developed by Darmadi (2013). This study used 12 Islamic Commercial Banks (BUS) with a total of 36 Annual Reports during the 2014-2016 period as samples. This study is written using a qualitative descriptive approach. The technique of data analysis is content analysis methods with dichotomous procedures. Based on the data analysis during the observation period, the results show that the ICG disclosure rate in the annual reports of Sharia Commercial Banks reaches an average score of 84.3% with a trend that increases per year. However, the improvement of the implementation of good corporate governance that in accordance with sharia principles must continue to be implemented by Islamic banks as a sharia entity to realize accountability to Allah SWT and to realize Maqashid Shariah.Keywords : Annual Report, Disclosures, Islamic banking, Islamic Corporate Govenance, Sharia Entity